Roadmap of China steel industry in the past 70 years. (26th November 2019) - Dong, Hongbaio; Liu, Yang; Wang, Lijun; Li, Xinchuang; Tian, Zhiling; Huang, Yixin; McDonald, Chris
ABSTRACT: The development of China's steel industry has been phenomenal, and in 2018, China's crude steel production reached 928.3 million tonnes and accounted for 51.3% share of global crude steel production. In the past 70 years, along with the country's growth and development, China steel industry has experienced a period of unstable development, rapid growth, reduction and optimization. The purposes of this article are to provide some historical background of the steel industry development in China. In this article, we will summarize the unstable development of China's steel industry from 1949 to 1978. We will, then, describe stable development over the reform and opening-up period from 1978 to 1999 and rapid development in the boom period from 2000 to 2014. Finally, we will discuss how the steel industry copes with the new challenges in China's move towards supply-side reform since 2015 and the future directions of the development of China's steel industry.